Climate data for Odesa, Ukraine in 2021–2050 based on EURO‐CORDEX simulations - Halyna Borovska; Valeriy Khokhlov (Geoscience Data Journal, 2024)
Abstract Climate change adaptation planning at the municipal level has become mandatory due to the increasing frequency of extreme weather and climate events. The availability of near‐future climate data is the first step towards creating an adaptation plan for a city. We created the CP_OdU (Climate Projections for Odesa, Ukraine) dataset, which contains daily output variables from the 102 model runs and monthly (yearly) indices calculated for 2021–2050 in the closest to Odesa land‐located model grid point. The future data are based on 26 and 76 simulations for the scenarios RCP4.5 and RCP8.5, respectively, of 14 RCMs from the EURO‐CORDEX project. The horizontal resolution of spatial grids in the RCMs is ~0.11° or ~12 km. The CP_OdU dataset contains 76 indices relating to cloudiness, wind parameters, relative humidity, precipitation amount, snow depth and temperature. A very short description of the near‐future climate in Odesa for the RCP8.5 scenario shows its trend towards a Mediterranean climate. The rising temperature supported by the change of intra‐annual variations of precipitation will result in hot, dry summers and mild, moderately wet winters. The CP_OdU dataset can be used by climate scientists, applied science engineers and climate stakeholders in society for the creation of a climate change adaptation plan for Odesa, Ukraine.